2007
DOI: 10.1080/15421400701732449
|View full text |Cite
|
Sign up to set email alerts
|

Kinked Focal Conic Domains in a SmA

Abstract: International audienceWe have investigated Focal Conic Domains (FCD) in several materials that have a transition from a SmA to a nematic phase (N): the focal lines are seldom an ideal ellipse and an ideal hyperbola, and suffer large transformations (in shape and in size) when approaching the transition to the nematic phase, or appear imperfect on cooling from the nematic phase. Some examples of these transformations are shown, including the temperature dependence of the ellipse diameter. Contrari- wise, FCDs r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the FCDs, the layers are folded into Dupin cyclides with ellipse and hyperbola which can be identified as disclinations. Kleman et al [ 47 ] and Meyer et al [ 48 ] experimentally observed that the interaction between FCDs and dislocations creates kinks on disclinations. As a result of this interaction, the screw dislocations will align along the kink.…”
Section: Defect Structures In the Smectic Phasementioning
confidence: 99%
See 1 more Smart Citation
“…In the FCDs, the layers are folded into Dupin cyclides with ellipse and hyperbola which can be identified as disclinations. Kleman et al [ 47 ] and Meyer et al [ 48 ] experimentally observed that the interaction between FCDs and dislocations creates kinks on disclinations. As a result of this interaction, the screw dislocations will align along the kink.…”
Section: Defect Structures In the Smectic Phasementioning
confidence: 99%
“…Moreover, the dynamic coupling between the dislocation loops and the shear flow may induce the distortion of the FCDs since the dislocation loops can adapt to the applied shear stress [ 38 ]. Kleman et al [ 47 ] and Meyer et al [ 48 ] indeed pointed out that the interaction of the FCDs with dislocations causes the distortion of the FCD shape. Detailed analysis on the eccentricity would clarify how the dislocation loops attribute to the FCD structure.…”
Section: Fcd Formation Induced By Shear Quenchmentioning
confidence: 99%
“…Note that in the limit that the blue sphere center moves off to infinity along real branch, it becomes a plane tangent to the cyclide, and the cone becomes an infinite cylinder. This construction is the basis for the construction of large angle grain boundaries ( 16 ) and can also give rise to spatially varying eccentricity in thick enough freestanding films ( 20 23 ) or by confining a hybrid-aligned smectic with curved interfaces ( 17 ) by manipulating interface behavior with colloidal particles. Note that a sphere centered on the virtual branch at the diametrically opposed infinity also is a plane tangent to the cyclide.…”
Section: Resultsmentioning
confidence: 99%
“…Imperfections in the ideality of FCDs have been recently investigated [9][10][11]; some of these are macroscopic, but most are microscopic, described as ''kinks''.…”
Section: Introductionmentioning
confidence: 99%